The equity impacts of bus rapid transit: A review of the evidence and implications for sustainable transport. Issue 2 (7th February 2018) - Venter, Christoffel; Jennings, Gail; Hidalgo, Darío; Valderrama Pineda, Andrés Felipe
ABSTRACT: The paper offers an analysis of empirical evidence on the equity impacts of operational Bus Rapid Transit (BRT) systems in the Global South. The focus is on vertical equity, i.e. whether BRT systems achieve progressive benefits for poorer segments of the population. Findings from Africa, Asia, and Latin America all suggest that BRT does offer significant benefits to low-income groups, in terms of travel time and cost savings, access enhancement, and safety and health benefits. However benefits are often skewed toward medium-income users and thus less progressive than they might be. Two primary reasons for this are insufficient spatial coverage and inappropriate fare policies. While many features of BRT potentially allow it to deliver pro-poor outcomes, such outcomes only materialize if BRT implementers pay specific and sustained attention to equity. The paper identifies key issues that need to be addressed to steer BRT implementation toward more socially sustainable outcomes—including better integration with other transit, paratransit, and nonmotorized transport services, and with the housing sector.